Layering of bidisperse charged nanoparticles in sedimentation. Issue 20 (13th May 2020) - Xu, Xufeng; Biesheuvel, P. M.; Cölfen, Helmut; Spruijt, Evan
Abstract : The layering of nanoparticles can be quantitatively in situ measured and tuned, which agrees very well with the theoretical calculations. Abstract : Bidisperse mixtures of charged nanoparticles form separate layers upon centrifugation as a result of minimization of the system's free energy in sedimentation-diffusion equilibrium. Different factors were investigated experimentally for their effects on the layering, and are supported by theoretical calculations of the full sedimentation profiles. Surprisingly, lighter/smaller nanoparticles can even sink below heavier/larger ones when the particle surface charge is carefully tuned. This study provides deeper insights into the control of layering in polydisperse particle mixtures during sedimentation.